STRUGGLE FOR REACHING A DREAM IN FYWELL'S ICE PRINCESS MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - MUNAWAROH, SHARA SITI (2010)
The major problem of this study is to reveal how struggle of Casey Carlyle is reflected in Ice Princess Movie directed Tim Fywells. The objectives of the study are to analyze the movie based on its structural elements and on the psychological analysis. In analyzing the movie, the researcher uses qualitative study. There are two kinds of data source. The primary data is the movie of Ice Princess, while the secondary data are books and internet websites related to the study. The method of collecting data is purpose sampling by watching carefully the movie and then the researcher took of sample dialogue and ellipse of picture of the movie then used it as a starting point to analyze the issue. The technique of data analysis is descriptive technique. A result of the analysis shows the following conclusion: first, Tim Fywell wants to utter his idea that struggle for reaching a dream should be achieved by sacrifice. Second, struggle for reaching a dream achieved by sacrifice will influence the psychological development of the major character. In this movie, Casey Carlyle as the major character has to struggle for reaching a dream as a professional skater to reinforce her psychological development.